The friction and wear behavior of Cu-Ni3Al composites by dry sliding - Demirel, Mehtap; Muratoglu, Mehtap (My University, 2011)
The suitability of Ni3Al intermetallics as reinforcements for Cu-base materials in tribological applications has been studied. For this purpose, Cu/Ni3Al (5 wt %, 10 wt % and 15 wt %) composites were prepared by powder-metallurgy techniques and tested on a pin-on-ring apparatus. The effects of the applied load (83-150 N) at a constant sliding velocity of 0.4 m/s on the wear behaviour of Cu-Ni3Al composites and wear mechanisms during dry sliding were investigated. The worn surfaces were examined by scanning electron microscopy (SEM) and energy-dispersive spectrometry (EDS). It was found that with increasing applied load, the weight loss of the composites increased to levels comparable to those of an unreinforced Cu matrix. In addition, the weight loss increased with the weight percentage of Ni3Al particles. The coefficients of friction for the composites increased with the increasing of the applied load and increased with increasing the weight percentage of the Ni3Al particulates. For a Cu-15wt % Ni3Al composite the weight fraction of reinforcement was critical, as it showed the highest wear rate for all the applied loads.
Keywords: Coefficient of friction; Copper; Metal-matrix composites; Ni3Al; Wear